Cytokine profile in patients with osteoarthritis after SARS-CoV-2 infection - KRENYTSKA, Daryna; KOT, Larysa; HALENOVA, Tetiana; RAKSHA, Nataliia; VOVK, Tetiana; SAVCHUK, Olexii; PELLICANO, Rinaldo; ABENAVOLI, Ludovico; FALALYEYEVA, Tetyana; OSTAPCHENKO, Liudmyla (Minerva Biotechnology and Biomolecular Research, 2022)
BACKGROUND: Severe acute respiratory syndrome-related Coronavirus 2 (SARS-CoV-2) іnfection induces a pro-inflammatory state of an organism with long-term systemic consequences as a result. Systemic inflammation, characterized by a high circulating level of inflammatory cytokines, is a significant factor influencing articular cartilage metabolism in osteoarthritis (OA). This study aimed to determine the levels of pro-inflammatory and anti-inflammatory cytokines in plasma of patients with OA following SARS-CoV-2 infection and to compare them with those of healthy controls. METHODS: The experiment involved patients of the Orthopedic Specialty Clinic aged 46 to 69 diagnosed with knee OA. Among persons with joint pathology a group of convalescent patients from 6-9 months after COVID-19 was identified. The control group involved relatively healthy donors. The plasma levels of pro-inflammatory (IL-1β, IL-6, IL-8, IL-12β, tumor necrosis factor α [TNF-α], interferon-gamma [IFN-γ]) and anti-inflammatory (IL-4 and IL-10) cytokines were determined by enzyme-linked immunosorbent assay. RESULTS: It was established that in patients with OA, as well as after suffering from SARS-CoV-2 infection, an increase in the plasma levels of IL-1β was observed against the background of a decrease in the levels of IL-4, IL-8, IL-10, IL- 12β, TNF-α and IFN-γ, compared to the healthy controls. COVID-19 more significantly influenced the plasma levels of pro-inflammatory cytokines IL-1β and IL-12β. CONCLUSIONS: The results indicate the imbalance of pro- and anti-inflammatory cytokines in the plasma in patients with OA for a long post-COVID. Сhanges in the levels of inflammatory mediators suggest distinct immunoregulatory mechanisms involved in the pathogenesis of both joint pathology and systemic disorders caused by SARS-CoV-2.